Optimal fiscal devaluation - François Langot; Lise Patureau; Thepthida Sopraseuth (Institute for the Study of Labor (IZA), 2012)
We study fiscal devaluation in a small-open economy with labor market search frictions. Our analysis shows the key role of both dimensions in shaping the optimal tax scheme. By reducing labor market distortions, the tax reform is welfare-improving. Yet, as it makes imports more expensive, fiscal devaluation lowers the agents' purchasing power, which is welfare-reducing. These contrasting effects give rise to an optimal tax scheme. Besides, transition matters. If the economy is better off in the long run, the required transitional saving effort increases the cost of the reform, thereby calling for a moderate magnitude of fiscal devaluation.
Keywords: E27; E62; H21; J38; 330; fiscal devaluation; consumption tax; payroll tax; labor market search; small open economy; Dynamic General Equilibrium model; Steuerreform; Optimale Besteuerung; Internationaler Wettbewerb; Kleines-offenes-Land; Arbeitsuche; Dynamisches Gleichgewicht; Theorie